2016
DOI: 10.1016/j.pec.2016.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and adherence to medical treatment in chronic and acute illness: A meta-analysis

Abstract: Objective To use meta-analytic techniques to assess average effect sizes in studies of: (1) the correlation between patient health literacy and both medication and non-medication adherence, and (2) the efficacy of health literacy interventions on improving health literacy and treatment adherence. Methods PsychINFO and PubMed databases were searched (1948–2012). A total of 220 published articles met the criteria for inclusion; effect sizes were extracted and articles were coded for moderators. Results Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
339
3
31

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 479 publications
(392 citation statements)
references
References 40 publications
19
339
3
31
Order By: Relevance
“…Our findings are consistent with that from a recent meta-analysis, which found a significant and positive relationship between health literacy and adherence with a 14% increased risk of non-adherence in those with lower health literacy [39]. Non-adherence rates were 1.33 times greater in those with limited health literacy [39]. A unique aspect of this study is the demonstration of this relationship with the HLQ, which is a contemporary tool compared to those used in previous studies (e.g.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with that from a recent meta-analysis, which found a significant and positive relationship between health literacy and adherence with a 14% increased risk of non-adherence in those with lower health literacy [39]. Non-adherence rates were 1.33 times greater in those with limited health literacy [39]. A unique aspect of this study is the demonstration of this relationship with the HLQ, which is a contemporary tool compared to those used in previous studies (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Six out of the nine factors emerged as [39] significantly correlated with self-reported medication adherence (Table 4). In each case, lower scores on these factors were related to poorer medication adherence.…”
Section: Resultsmentioning
confidence: 99%
“…33 These findings are in accordance with reviews which advocated that health literacy in itself cannot account for medication adherence, but that other variables should also be taken into consideration. 7,8,34 We suggest that self-efficacy is an important mediator of the effect of health literacy on medication adherence. Moreover, besides health literacy and self-efficacy, patients’ acceptance of their doctor’s advice was a covariate in the present model, so it is also an important factor in terms of medication adherence.…”
Section: Resultsmentioning
confidence: 86%
“…However, the evidence is mixed concerning cardiovascular patients, as some studies reported that low health literacy was associated with poor adherence, while others studies found no significant relationship. 7,8 It is worth noting that the majority of the studies operationalized health literacy as basic numeracy and reading skills or health-related knowledge, but relatively little research has been done on its complex cognitive components, such as judgment skills. The term judgment skills refers to one’s ability to examine one’s own capabilities and limitations in order to make appropriate health decisions.…”
Section: Introductionmentioning
confidence: 99%
“…This finding concurs with other studies that showed that a substantial proportion of Thai patients have inadequate health literacy, including knowledge about medication used in various chronic diseases, such as hypertension18 and schizophrenia 19. This problem needs to be addressed, as health literacy is positively associated with medication adherence 20,21…”
Section: Discussionmentioning
confidence: 99%